A mathematical model for the dynamics of banana Xanthomonas Wilt with vertical transmission and inflorescence infection - Nakakawa, J.; Mugisha, J.Y.T.; Shaw, M.W.; Karamura, E.B. (World Scientific Publishing, 2016)
A mathematical model for Banana Xanthomonas Wilt (BXW) spread by insect vector is presented. The model incorporates inflorescence infection and vertical transmission from the mother corm to attached suckers, but not tool-based transmission by humans. Expressions for the basic reproduction number [Formula: see text] are obtained and it is verified that disease persists, at a unique endemic level, when [Formula: see text]. From sensitivity analysis, inflorescence infection rate and roguing rate were the parameters with most influence on disease persistence and equilibrium level. Vertical transmission parameters had less effect on persistence threshold values. Parameters were approximately estimated from field data. The model indicates that single stem removal is a feasible approach to eradication if spread is mainly via inflorescence infection. This requires continuous surveillance and debudding such that a 50% reduction in inflorescence infection and 2–3 weeks interval of surveillance would eventually lead to full recovery of banana plantations and hence improved production.